2011
DOI: 10.1016/j.chemgeo.2010.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic evidence for the infiltration of mantle and metamorphic CO2–H2O fluids from below in faulted rocks from the San Andreas Fault system

Abstract: To characterize the origin of the fluids involved in the San Andreas Fault (SAF) system, we carried out an isotope study of exhumed faulted rocks from deformation zones, vein fillings and their hosts and the fluid inclusions associated with these materials. Samples were collected from segments along the SAF system selected to provide a depth profile from upper to lower crust. In all, 75 samples from various structures and lithologies from 13 localities were analyzed for noble gas, carbon, and oxygen isotope co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 57 publications
(72 reference statements)
3
16
0
Order By: Relevance
“…The latter geometry would lead to a narrow depth range for release of fluids and metals at shallow levels, which were channeled into an eventual frozen and non-convecting mantle wedge that was itself devolatilized during eventual sinking of the slab. This is again a hypothetical model that cannot be proven using any unequivocal analytical data available, although radiogenic isotope, halogen, and noble gas data are taken as indicative of such in many studies (see above) and studies of these components in many crustalscale fault zones, such as the San Andreas fault system (Kennedy and van Soest, 2007;Pili et al, 2011) and Karakorum fault (Klemperer, 2013), indicate that mantle fluids reach the shallow crust. The attraction of such a model as was proposed for the Jiaodong deposits is that orogenic gold deposits inevitably form due to heating of new crust and such crust is always being subducted in the tectonic setting defined for orogenic gold, suggesting a fundamental connection.…”
Section: Accepted Manuscriptmentioning
confidence: 96%
“…The latter geometry would lead to a narrow depth range for release of fluids and metals at shallow levels, which were channeled into an eventual frozen and non-convecting mantle wedge that was itself devolatilized during eventual sinking of the slab. This is again a hypothetical model that cannot be proven using any unequivocal analytical data available, although radiogenic isotope, halogen, and noble gas data are taken as indicative of such in many studies (see above) and studies of these components in many crustalscale fault zones, such as the San Andreas fault system (Kennedy and van Soest, 2007;Pili et al, 2011) and Karakorum fault (Klemperer, 2013), indicate that mantle fluids reach the shallow crust. The attraction of such a model as was proposed for the Jiaodong deposits is that orogenic gold deposits inevitably form due to heating of new crust and such crust is always being subducted in the tectonic setting defined for orogenic gold, suggesting a fundamental connection.…”
Section: Accepted Manuscriptmentioning
confidence: 96%
“…[53] If fluid entering the fault zone is assumed to have had constant isotopic composition [Hausegger et al, 2010;Molli et al, 2010], the relative position of individual data points in the d 13 C-d 18 O diagram (Figure 7) may relate to variations in the amount of fluid interacting with the sample [Kirschner and Kennedy, 2001;Pili et al, 2002Pili et al, , 2011. Large breccia fragments with isotopic values near the protolith interacted with small quantities of fluid.…”
Section: C-d 18 O Distribution and Related Modelingmentioning
confidence: 99%
“…Using bulk rock chemical analysis, Goddard and Evans [] concluded that fluids passing through fault zones react with the fault rock, dissolving and transporting soluble cations away. Such an effect can change fault rock volume, insoluble content and isotopic composition, as well as transport and mechanical properties [ Labaume et al ., ; Chen et al ., ; Molli et al ., ; Pili et al ., , ]. Similarly, fluid‐assisted mineralogical changes may cause fault weakening and reactivation [e.g., Chester et al ., ], particularly when clay minerals are formed [e.g., Wintsch et al ., ; Vrolijk and van der Pluijm , ].…”
Section: Introductionmentioning
confidence: 99%
“…Separating the relative proportions of mantle and crustal carbon is possible through investigation of the isotopic composition of emitted carbon (e.g., Chiodini et al 2011) and is increasingly important given that during eruptions magmatic intrusions may interact with crustal material, strongly enhancing the CO 2 output of the volcanic system (Troll et al 2012), at least temporarily. The magnitude of diffuse mantle CO 2 can also be identified isotopically in mixed metamorphic and magmatic gases using Carbon (Chiodini et al 2011) or Helium isotopes as a proxy for deep mantle sources in both major fault systems (Pili et al 2011) and crustal tectonic structures (Crossey et al 2009).…”
Section: Introduction: Volcanic Co 2 Emissions In the Geological Carbmentioning
confidence: 99%